Impact analysis of battery control strategies on battery aging for grid-connected and solar-powered residential battery applications - Terkes, Musa; Demirci, Alpaslan; Gokalp, Erdin; Cali, Umit (CELL PRESS, 2025)
How can battery control approaches for minimum-cost household prosumers improve the supplydemand balance from a technical, economic, and environmental perspective? Moreover, how effective is the ratio of photovoltaic energy production to load consumption in the cost-benefit relationship of control strategies? What are the effects of control strategies on battery health? To answer these questions, this paper compares the feasibility of self-consumption and feed-in damping control strategies developed with a minimum cost objective for battery storage and rooftop solar photovoltaic panel integrated household consumers with different load cover ratios and fraction of energy production to load. The control methods consider the annual operational aspects of storage awareness of battery aging using Gurobi solver. The results show that the feedin damping approach will reduce curtailment energy by up to 15.6 %, with a cost up to 5.64 % lower. Thus, it reduces annual battery aging and can increase useful life by up to 1.87 years compared to self-consumption strategy, assuming 50 % end-of-life. Moreover, a lower energy production to load ratio can improve battery health by reducing the number of charge-discharge cycles. This approach helps to reduce curtailment energy by up to 8.35 %, but it also leads to an increase in carbon emissions by up to 0.774 tons per year and an increase in energy costs by up to 0.053 $/kWh. Optimal battery control strategies can enhance energy sustainability and environmental performance while improving stakeholders' energy economics.
Keywords: Battery control strategies; Degradation costs; Battery aging; Calendar and cycle degradation; Energy management; Microgrid; ENERGY MANAGEMENT STRATEGY; STORAGE-SYSTEMS; OPERATIONAL STRATEGIES; SELF-CONSUMPTION; OPTIMIZATION; PERFORMANCE; CAPACITY; Science & Technology - Other Topics